Junior gymnastic: incidence and injury profile - Bolling, C.; Leite, M.; Reis, D. (British Journal of Sports Medicine, 2014)
Background: Junior is the transition to senior category reflected by training load increase and element's difficulty. The higher physical demands modify the injury profile. Objective: The aim of this study was to describe junior gymnasts' injury profile in the seasons 2011-2012 in a sports club. Design: This is an observational study, transversal, about the injuries in 2011-2012 season. Setting: This study was developed with national and international level gymnasts, in a Brazilian sports club. Participants: The sample was composed of 6 junior male gymnasts, mean age of 15.8 years, exposed to the same training load. Risk factor assessment: The physiotherapist reported all injuries during the season. The injury definition was time loss and/or any symptom that result in a training modification. Main outcome measurements: The injuries were reported related to type (acute/chronic), location, affected structure and injury mechanism. Results: The injury incidence was 37 in 2 years, with an annual average of 3.08 injuries/athlete. According to the injury type, acute lesions were 46% and 54% chronic. The most affected location was the upper limbs (56%), highlighting the shoulder (29%). Shoulder injuries were 18% in 2011 and 21% in 2012, and elbow injuries indicate a decrease from 13% to 4%. In lower limbs (24%), ankle was the more affected joint (10%). Tendon was most common injured structure (32%) followed by muscular (18%). The most frequent mechanism was tendinopathy, especially rotator cuff tendons. Conclusion: Gymnastic's injury profile highlights the demand on upper limbs. The higher shoulder injuries incidence are associated to greater difficulty in pommel horse, rings, parallel bars, and horizontal bar. Lower elbow injuries reflect a technique improvement. Ankle injuries incidence are associated to repeated jumps and landings. Junior injury profile is important to guide the prevention strategies for healthy senior athletes.